“THE HEART OF IRISH-LANGUAGE PROVERBS”: A LINGUO-STYLISTIC ANALYSIS OF EXPLICIT METAPHOR - Mac Coinnigh, Marcas (Proverbium - Yearbook, 2013)
Metaphor has featured frequently in attempts to define the proverb (see Taylor 1931, Whiting 1932, Mieder 1985, 1996), and since the advent of modern paremiological scholarship, it has been identified as one of the most salient markers of ‘proverbiality’ (Arora 1984) across a broad spectrum of world languages. Significant language-specific analyses, such as those by Klimenko (1946), Silverman-Weinreich (1981), and Arora (1984) have provided valuable qualitative information on the form and function of metaphor in Russian, Yiddish, and Spanish proverbs respectively. Unfortunately, no academic scholarship has engaged with the sub-ject of metaphor in Irish proverbs. This study builds on international paremiological research on metaphor and provides for the first time a comprehensive quantitative and qualitative analysis of the form, frequency, and nature of linguistic metaphors in Irish proverbs (1856-1952). Moreover, from the perspective of paremiology, it presents a methodological template and result-set that can be applied cross-linguistically to compare metaphor in the proverbs of other languages.